SMC based DTC-SVM control of five-phase permanent magnet synchronous motor drive - Fayçal Mehedi; Rachid Taleb; Abdelkadir Belhadj Djilali; Adil Yahdou (Institute of Advanced Engineering and Science, 2020)
This article presents an improved direct torque control (DTC) technique with space vector modulation (SVM) for a five-phase permanent magnet synchronous motor (PMSM) using a sliding mode speed control (SMC).The proposed control scheme of the five-phase PMSM combines the advantages of SMC control and the SVM algorithm. The SMC method insensitive to uncertainties, in particular external disturbances and parameter variations. In this paper, the SMC controller is used to control the rotor speed of the five-phase PMSM based on DTC-SVM. The rotor speed response, torque and stator flux are determined and compared with traditional control method. The simulations results confirm the validity and effectiveness of the proposed control technique in terms of performance and robustness against machine parameter variations (inertia variation). The efficiency of the proposed method applied on the five-phase PMSM is verified by the MATLAB/Simulink.